THE USE OF TOCILIZUMAB IN SEVERE COVID-19: A COMPREHENSIVE REVIEW : Tocilizumab and severe COVID-19 - Milošević, Ivana; Beronja, Branko (Medical Research, 2024)
This review delves into the therapeutic utility of Tocilizumab (TCZ) in COVID-19, specifically examining its mechanisms, safety considerations, clinical effectiveness, dosage strategies, and outcomes within the Serbian context. TCZ, acting as an IL-6 receptor inhibitor, addresses the cytokine storm prevalent in severe cases, leveraging its distinctive structure and nonlinear pharmacokinetics. While overall safety profiles indicate tolerability, there are nuanced concerns in critically ill patients. Clinical trials, marked by variability, underscore the necessity for nuanced interpretation. Current Serbian protocols advocate TCZ usage based on IL-6 levels, suggesting a pragmatic 400 mg dose during shortages. Optimal initiation timing aligns with the inflammatory phase (days 7-10 post-symptoms), with patient selection emphasizing biomarkers, disease severity, and respiratory support. The combination of TCZ with corticosteroids reveals mortality reduction, necessitating judicious dosing. Potential benefits emerge from TCZ combinations with remdesivir, NSAIDs, and anticoagulants, warranting cautious dosing and vigilant monitoring. Retrospective studies in Serbia report positive outcomes, accentuating TCZ's potential in managing severe cases. In summation, TCZ exhibits promise in COVID-19 treatment, demanding ongoing research and meticulous patient management, particularly in resource-challenged environments.
Keywords: Tocilizumab, severe COVID-19, effectiveness, safety, experiences